Optimalisasi Layanan Operasional Bus Trans Binjai Dalam Upaya Meningkatkan Pelayanan Publik Di Kota Binjai - ali, khaidir (UNIVERSITAS ISLAM SYEKH YUSUF, 2023)
Transportation is a component of road traffic and transportation that contributes to the improvement of general welfare. The Minister of Transportation and the Mayor of Binjai inaugurated the operation of the Trans Binjai Bus in September 2017. This study aims to evaluate the quality of Trans Binjai Bus operational services in an effort to improve public services in Binjai City. To ensure customer satisfaction, the service quality included is used to improve community service. Qualitative method with descriptive analysis is used in this study to obtain a systematic, factual and accurate description of the problem under study. The results of the study show that the operational quality of Trans Binjai Bus services has been carried out quite well and as much as possible, using a lot of manual methods. The results show that a more modern and application-based concept should be applied to improve services